2010
DOI: 10.1093/europace/euq167
|View full text |Cite
|
Sign up to set email alerts
|

Can optimization of pacing settings compensate for a non-optimal left ventricular pacing site?

Abstract: Optimization of the AVD and VVD can partly compensate for a non-optimal LV pacing site. However, a combination of an optimal LV pacing site and optimized pacing settings gives the best acute haemodynamic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…2 For standard CRT delivery, the atrioventricular pacing interval is shortened to ensure consistent left ventricular (LV) and right ventricular (RV) capture. However, it has been suggested that in addition to the activation wavefronts generated by RV and LV pacing, the physiological activation propagated through the right bundle branch may be part of the resynchronization mechanism.…”
mentioning
confidence: 99%
“…2 For standard CRT delivery, the atrioventricular pacing interval is shortened to ensure consistent left ventricular (LV) and right ventricular (RV) capture. However, it has been suggested that in addition to the activation wavefronts generated by RV and LV pacing, the physiological activation propagated through the right bundle branch may be part of the resynchronization mechanism.…”
mentioning
confidence: 99%
“…Determination of the pacing site is most important for the efficacy of CRT. 2 In the present case, intraoperative 2-dimensional epicardial echocardiographic measurement of circumferential strain enabled us to precisely identify the most delayed and earliest contraction points. We could also evaluate the increase in systemic blood pressure and the improvement in synchrony on a real-time basis.…”
mentioning
confidence: 72%
“…The study of Bogaard and associates reported that the optimal VV delay is -30 ms (-60 ms to 5 ms) and -20 ms (-40 ms to 0 ms) at non-optimal and optimal LV lead sites, respectively [29]. Heinroth and associates compared VV delays and reported that LV preexcitation by 40 ms resulted the largest mean CO, and similar values were obtained with LV preexcitation by 20 ms and 60 ms [10].…”
Section: Vv Delaymentioning
confidence: 86%